2022
DOI: 10.1007/s11071-022-07680-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and integrability of the swinging Atwood machine generalisations

Abstract: This paper studies the dynamics and integrability of two generalisations of a 3D Swinging Atwood’s Machine with additional Coulomb’s interactions and Hooke’s law of elasticity. The complexity of these systems is presented with the help of Poincaré cross sections, phase-parametric diagrams and Lyapunov exponents spectrums. Amazingly, such systems possess both chaotic and integrable dynamics. For the integrable cases we find additional first integrals and we construct general solutions written in terms of ellipt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The literature on the existence and nonexistence of first integrals or generally the integrability problem of a dynamical system is one of the main open problems in the qualitative theory of differential systems, see [1,2,3,4]. Many non-linear dynamical systems arise in physical and electrical engineering, etc.…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…The literature on the existence and nonexistence of first integrals or generally the integrability problem of a dynamical system is one of the main open problems in the qualitative theory of differential systems, see [1,2,3,4]. Many non-linear dynamical systems arise in physical and electrical engineering, etc.…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…Because of this, many new integrable and super-integrable systems were found [64][65][66]. To exemplify it, we mention two generalizations of the swinging Atwood machine model recently studied in [24,28]. In this paper, the authors performed a detailed integrability analysis and found integrable and super-integrable cases with additional first integrals quadratic and quartic in the momenta.…”
Section: Theorem 11 (Morales-ramis (1999)) If a Hamiltonian System Is...mentioning
confidence: 99%
“…Currently, there is great activity studying variable-length pendulum systems, such as the swinging Atwood machine [27] and its generalizatins [28], the variable-length coupled pendulums recently studied in [24], or the double variable-length pendulum with counterweight mass [71][72][73]. Variable-length pendulum systems are excellent examples for studying nonlinear dynamics, chaos, and bifurcations.…”
Section: Theorem 11 (Morales-ramis (1999)) If a Hamiltonian System Is...mentioning
confidence: 99%
See 1 more Smart Citation